Biochemical Validation of a Fourth Guanidine Riboswitch Class in Bacteria - Salvail, Hubert (Biochemistry, 2020)
An intriguing consequence of ongoing riboswitch discovery efforts is the occasional identification of metabolic or toxicity response pathways for unusual ligands. Recently, we reported the experimental validation of three distinct bacterial riboswitch classes that regulate gene expression in response to the selective binding of a guanidinium ion. These riboswitch classes, called guanidine-I, -II and -III, regulate numerous genes whose protein products include previously misannotated guanidine exporters and enzymes that degrade guanidine via an initial carboxylation reaction. Guanidine is now recognized as the primal substrate of many multidrug efflux pumps that are important for bacterial resistance to certain antibiotics. Guanidine carboxylase enzymes had long been annotated as urea carboxylase enzymes but are now understood to participate in guanidine degradation. Herein we report the existence of a fourth riboswitch class for this ligand, called “guanidine-IV”. Members of this class use a novel aptamer to selectively bind guanidine and use an unusual expression platform arrangement that is predicted to activate gene expression when ligand is present. The wide distribution of this abundant riboswitch class, coupled with the striking diversity of other guanidine-sensing RNAs, demonstrates that many bacterial species maintain sophisticated sensory and genetic mechanisms to avoid guanidine toxicity. This finding further highlights the mystery regarding the natural source of this nitrogen-rich chemical moiety.